Adsorption of synthetic dye by using agricultural by-product - Saiful Rafiuddin Mohamad, 1989-; Tony Hadibarata, supervisor; Fakulti Kejuruteraan Awam (2012)
Project Paper (Sarjana Muda (Awam - Alam Sekitar)) - Universiti Teknologi Malaysia, 2012